Dinamika Perkembangan Bahasa Arab Periode Awal Islam: Kajian Perspektif Historis - Sintaria Marsela Marsela; Robi irawan; Nur Fatimatuzzahroh; Muhammad Afif Amrulloh (Al-Kindi, 2025)
This study aims to analyze and describe the dynamics of Arabic language development in the early Islamic period (7th to 8th centuries AD). In contrast to its status in the Jahiliyyah era as a tribal spoken language, Arabic transformed into a language of administration, science, and most importantly, a sacred language, along with the expansion of the Caliphate. The main focus of this study is the central role of the Qur'an as a linguistic catalyst, which not only established the Quraysh dialect as Al-Lughah al-Fushah (Classical Standard Arabic) but also encouraged efforts for comprehensive linguistic codification. The method used is historical-linguistic, which involves a chronological review of key events and linguistic analysis of primary texts (the Qur'an) and secondary sources (early grammatical works). The findings indicate that increased linguistic contact after the conquest led to the emergence of the phenomenon of lahn (grammatical errors), which motivated scholars such as Abu al-Aswad al-Du'ali and Sibawayhi to establish grammatical rules (Nahw and Sarf). This process of codification succeeded in creating a strict and stable linguistic standard, known as Classical Arabic.